SEMIOTICS IN INTERPERSONAL COMMUNICATION OF TRADITIONAL MARKET TRADERS IN MEDAN CITY: A PRAGMATIC PERSPECTIVE - Ezir, Ely; Marpaung, Devi Annisa; Nasution, Aisyah Noor; Apriliyanti, Apriliyanti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study investigates the role of semiotics in the interpersonal communication of traders in traditional markets in Medan City through a pragmatic lens. Semiotics, as the study of signs and symbols, plays a central role in shaping meaning and mutual understanding in everyday interactions. Traditional markets offer a rich communicative environment where traders and buyers depend not only on verbal exchanges but also on gestures, intonation, cultural codes, and symbolic expressions to negotiate meaning and sustain social relationships. This research adopts a qualitative descriptive design involving 20 traders selected purposively from three major traditional markets in Medan. Data were collected through participant observation and in-depth semi-structured interviews to capture authentic communicative behaviors and interpretations of meaning. The data were analyzed using semiotic and pragmatic frameworks to identify the implicit functions of signs and contextual negotiation of meaning in interpersonal exchanges. The findings reveal that semiotic elements in traders’ communication function to build trust, strengthen social solidarity, and create persuasive strategies that influence economic decision-making. From a pragmatic standpoint, meaning is constructed contextually, reflecting the traders’ cultural values, social norms, and economic intentions. The study concludes that semiotic practices in traditional market communication represent not only linguistic phenomena but also socio-cultural strategies that sustain market interactions and preserve local wisdom. These insights contribute to a deeper understanding of interpersonal communication as a dynamic process supporting the cultural and economic vitality of local communities.